2014
DOI: 10.3390/aerospace1020052
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vibrations and Emissions of Conventional Jet Fuel with Stressed 100% SPK and Fully Formulated Synthetic Jet Fuel

Abstract: Abstract:The rapid growth of the aviation sector around the globe has witnessed an overwhelming impact on fossil fuel resources. With the implementation of stricter environmental laws over emissions by conventional jet fuels, growing demand for research on alternative fuels has become imperative. One-hundred percent Synthetic Paraffinic Kerosene (SPK) and Fully Formulated Synthetic Jet Fuel have surfaced as viable alternatives for gas turbine engines due to their similar properties as that of Jet Fuel. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Researchers have done various studies on the use of alternative fuels in gas turbines, both for military and commercial aviation (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) . It has also been observed in various studies that there is an advantage in using alternative blends for gas turbines as the use of paraffinic alternative fuels aids in reducing the net carbon footprint, particulate and smoke emissions (27)(28)(29)(30)(31)(32) . This can also contribute to improving the local air quality (14,15,(19)(20)(21)(22)(23)(24)(25) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have done various studies on the use of alternative fuels in gas turbines, both for military and commercial aviation (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) . It has also been observed in various studies that there is an advantage in using alternative blends for gas turbines as the use of paraffinic alternative fuels aids in reducing the net carbon footprint, particulate and smoke emissions (27)(28)(29)(30)(31)(32) . This can also contribute to improving the local air quality (14,15,(19)(20)(21)(22)(23)(24)(25) .…”
Section: Introductionmentioning
confidence: 99%
“…Lobo et al (28) studied the effect of fuels derived from alternative sources on non-volatile particulate matter (PM) emissions. In recent years, studies have presented results on vibrational and noise production while using alternative fuels (29,30,33) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khandelwal et al found that a 100% synthetic kerosene showed more functioning stability in vibration than Jet-A1 and that it had the benefit of reduced emissions (8). They also discussed the possibility of reducing the use of aromatics during operation of the turbine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aromatics, volume% 2. Aromatics, volume% Sulfur, mercaptan, mass% (Khandelwal et al, 2014) The exact mechanism that leads to the creation of deposits is unknown, but it is widely attributed to the aromatic and heteroatomic species within the fuel (Jain & Sharma, 2011). The combustion and the turbine sections will receive the most impact, and it might cause engine malfunction, and in severe cases, the turbine damage may lead to catastrophic engine failure (Wanyan et al, 2010).…”
Section: Compositionmentioning
confidence: 99%